2014
DOI: 10.1111/1574-6941.12339
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community structure and dissolved organic matter in repeatedly flooded subsurface karst water pools

Abstract: Bacterial diversity, community assembly, and the composition of the dissolved organic matter (DOM) were studied in three temporary subsurface karst pools with different flooding regimes. We tested the hypothesis that microorganisms introduced to the pools during floods faced environmental filtering toward a 'typical' karst water community, and we investigated whether DOM composition was related to floodings and the residence time of water in stagnant pools. As predicted, longer water residence consistently led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 72 publications
(102 reference statements)
6
35
0
Order By: Relevance
“…The strongly-smelling alluvial sediments in these caves contain pieces of wood, foliage, and pine-needles mixed together with sand, and was studied by Kriz (1891;1892). The impact of alluvial sediments on geomicrobiology was investigated recently by Shabarova et al (2014). This study verified the hypothesis that the long-term residence of water in stagnant cave pools consistently led to a decline in bacterial diversity.…”
Section: Discussionsupporting
confidence: 72%
“…The strongly-smelling alluvial sediments in these caves contain pieces of wood, foliage, and pine-needles mixed together with sand, and was studied by Kriz (1891;1892). The impact of alluvial sediments on geomicrobiology was investigated recently by Shabarova et al (2014). This study verified the hypothesis that the long-term residence of water in stagnant cave pools consistently led to a decline in bacterial diversity.…”
Section: Discussionsupporting
confidence: 72%
“…The increase in the C/A C ratio in the bulk of the samples suggests that the humic-like material at the water table comprises more humified, older organic molecules compared to the majority of the samples from the surface. This is similar to results for shallow stagnant cave pools where the microbial decomposition of organic matter transforms it to a more stable refractory form in older waters (Shabarova et al 2014). The increase in the C/A C ratio may indicate the longer residence time, and thus greater age, of groundwater at the top of the freshwater lens, compared to waters interacting with vegetation, the land surface and vadose zone during rapid recharge.…”
Section: Groundwater From Boreholes and Trenchessupporting
confidence: 81%
“…Recently, Shabarova et al (2014) showed a significantly decrease in concentration of humic and fulvic acids in cave pools, over a period of weeks, as a result of microbial activity. Our data demonstrate that fresh organic matter derived from terrestrial plants (e.g.…”
Section: Microbial Response To Recharge Watersmentioning
confidence: 99%
“…This finding is important for the practical application in specific ecosystems in which DOC quality and concentrations may vary substantially. 37 Hence, the results above showed that DOC recovery and structures were quite uniform up to a DOC/PPL mass ratio of 1:200. We then have investigated the effects of variable DOC concentration at a fixed volume (6.25 mL) of SR DOM solution.…”
Section: Analytical Chemistrymentioning
confidence: 77%